Effects of Ambient Sensing on SiOx-Based Resistive Switching and Resilience Modulation by Stacking Engineering. (4th July 2018) - Chen, Ying-Chen; Huang, Hui-Chun; Lin, Chih-Yang; Kim, Sungjun; Chang, Yao-Feng; Lee, Jack C.
Abstract : The SiOx -based resistive random access memory (RRAM) is reported as the gas sensor with the spontaneous response i.e. memory window closure as air-vacuum switches, meanwhile enlarged the switching voltages in the vacuum. The HfOx /SiOx stacked structure is proposed with a superior resilience with response to ambient changes through inserting an interface structure, which attributed to the gain of the source of high defect density and Hf-encapsulation of the filamentary region as compared to single layer SiOx structures. Besides, the intrinsic nonlinear behavior is demonstrated by integrating a low dielectric layer, which suppresses the sneak path issues for large-scale SiOx -based RRAM crossbar array implementation in near future.